Маніпуляція в телефонному консультуванні - Карковська, Р. (Соціогуманітарні проблеми людини, 2010)
Розглянуто зміст та особливості маніпулятивного впливу, до яких належать прихованість мети та засобів маніпулянта і прийняття адресатом на себе відповідальності за події. Проаналізовано причини усвідомлюваного та неусвідомлюваного суб’єктом маніпулювання. Розкрито специфіку маніпулятивного впливу в телефонному консультуванні. Вивчено основні типологічні особливості абонентів, які маніпулюють під час телефонного діалогу. Подано аналіз доступних консультанту телефону довіри способів пасивного та активного захисту від маніпуляції абонентів. Розглянуто особливості прихованого впливу, який здійснює консультант на абонента через використання в діалозі навичок активного слухання. Обґрунтовано неприпустимість використання консультантом телефону довіри контрманіпуляції як форми активного захисту від прихованого впливу абонента. Contents and features of manipulating infl uence, to which belong hidden aims and facilities of manipulator and acceptance by an addressee the responsibility for that which takes place, are considered in the article. Reasons of realization by the subject of infl uence realized and unrealized manipulation are analysed. The specifi city of manipulating infl uence is exposed in the telephone advising. The basic typology features of subscribers, which manipulate during a telephone dialogue, are analysed. The analysis of accessible to the consultant of telephone of trust methods of the passive and active protecting from manipulating infl uence of subscribers is carried out. The features of the hidden infl uence which the consultant carries out on a subscriber through the use in the dialogue the skills of active listening are considered. Impermissibility of the use by the consultant of telephone of trust the reverse manipulation as a form of active protection against the hidden infl uence of subscriber is considered.